Impacts on older people contributing to an intergenerational course about aging. Issue 3 (3rd July 2019) - Tullo, Ellen StClair; Wakeling, Luisa Anne; Elliott, Anna
ABSTRACT: Newcastle University offers undergraduate students an opportunity to interact with older people by undertaking an intergenerational course about aging. This study systematically evaluated the impacts of involvement in the course on the older adults who participate using a framework analysis method. Three key themes relating to impact emerged: 'Learning, ' 'Barriers, ' and 'Contributing.' Participation largely led to beneficial impacts on older people through increased knowledge, identity work and generativity, although some examples of potentially negative outcomes were also suggested. These findings support and add to the growing evidence base concerning the outcomes of intergenerational education programs.